The Exploration of miRNAs From Porcine Fallopian Tube Stem Cells on Porcine Oocytes - Fu, Tzu-Yen; Wang, Shu-Hsuan; Lin, Tzu-Yi; Shen, Perng-Chih; Chang, Shen-Chang; Lin, Yu-Han; Chou, Chih-Jen; Yu, Yu-Hsiang; Yang, Kuo-Tai; Huang, Chao-Wei; Shaw, Steven W.; Peng, Shao-Yu (Frontiers in Veterinary Science, 2022)
Fallopian tube is essential to fertilization and embryonic development. Extracellular vesicles (EVs) from fallopian tube containing biological regulatory factors, such as lipids, proteins and microRNAs (miRNAs) serves as the key role. At present, studies on oocytes from porcine oviduct and components from EVs remain limited. We aim to explore the effect of EVs secreted by porcine fallopian tube stem cells (PFTSCs) on oocyte. When the fifth-generation PFTSCs reached 80-90% of confluency, the pig in vitro maturation medium was utilized, and the conditioned medium collected for oocyte incubations. To realize the functions of EVs, several proteins were used to determine whether extracted EVs were cell-free. Field emission scanning electron microscope and nanoparticle racking analyzer were used to observe the morphology. By next generation sequencing, 267 miRNAs were identified, and those with higher expression were selected to analyze the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment maps. The selected miR-152-3p, miR-148a-3p, miR-320a-3p, let-7f-5p and miR-22-3p, were predicted to target Cepb1 gene affecting MAPK pathway. Of the five miRNAs, miR-320a-3p showed significant difference in maturation rate in vitro maturation. The blastocyst rate of pig embryos was also significantly enhanced by adding 50 nM miR-320a-3p. In vitro culture with miR-320a-3p, the blastocyst rate was significantly higher, but the cleavages rate and cell numbers were not. The CM of PFTSCs effectively improve porcine oocyte development. The miRNAs in EVs are sequenced and identified. miR-320a-3p not only help the maturation, but also increase the blastocyst rates.